2018
DOI: 10.1039/c8nj00166a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preorganization in the chelation of UO22+by hydroxamate ligands: cyclic PIPOvs.linear NMA

Abstract: Thanks to preorganization, 1,2-PIPOH, the six-membered ring cyclic hydroxamic acid, binds uranyl six times more strongly than its linear, methyl-substituted homolog (NMAH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 74 publications
2
26
0
Order By: Relevance
“…The main difference between DFO* and DFOcyclo* is the cyclic structure of the additional hydroxamic acid group derived from 1,2-PIPOH. While open-chain hydroxamic acids, including DFO, are known to exist as a mixture of two E ( trans ) and Z ( cis ) isomers [2830], the Z configuration of the hydroxamate group is imparted by the cyclic structure of PIPO - , and is obviously more favourable for Zr 4+ coordination and could therefore result in a more stable complex [31]. The crystal structure of a Zr 4+ complex in which the metal is coordinated by four 1,2-PIPO - chelates has been reported previously [32].…”
Section: Resultsmentioning
confidence: 99%
“…The main difference between DFO* and DFOcyclo* is the cyclic structure of the additional hydroxamic acid group derived from 1,2-PIPOH. While open-chain hydroxamic acids, including DFO, are known to exist as a mixture of two E ( trans ) and Z ( cis ) isomers [2830], the Z configuration of the hydroxamate group is imparted by the cyclic structure of PIPO - , and is obviously more favourable for Zr 4+ coordination and could therefore result in a more stable complex [31]. The crystal structure of a Zr 4+ complex in which the metal is coordinated by four 1,2-PIPO - chelates has been reported previously [32].…”
Section: Resultsmentioning
confidence: 99%
“…All thermodynamic complex formation studies were performed in 0. The detailed procedure and equipment used to perform potentiometric and direct spectrophotometric titrations has been described in detail elsewhere (Sornosa-Ten et al, 2018).…”
Section: Thermodynamic Complexation Studiesmentioning
confidence: 99%
“…have also shown that thorium binding gives rise to a typical band centered at 230 nm ( ε = 17 600 M −1 cm −1 ), with a significant absorption around 200 nm [29]. Accordingly, an experimental ACE setup equipped with an UV detector could be used to monitor the migration in the capillary, despite the fact that thorium(IV) is spectroscopically silent, unlike uranium(VI) [6,44]. Hence, all injected samples contained a fixed amount of ligand (10 –4 M), while runs were made in triplicates using HClO 4 /NaClO 4 solutions as BGE ( I = 0.1 M) containing increasing amounts of thorium(IV) (0–5 × 10 –3 M).…”
Section: Resultsmentioning
confidence: 99%
“…In that respect, attempts to use ESI‐MS have been reported [3‐5]. In spite of the mild ionization processes and rapid solvent evaporation in the source, both the abundance and nature of the gas‐phase species do not necessarily mirror the solution speciation at a given concentration level [6,7], as equilibria for labile species are displaced while droplets are concentrating.…”
Section: Introductionmentioning
confidence: 99%